2021
DOI: 10.1371/journal.pone.0253329
|View full text |Cite
|
Sign up to set email alerts
|

The selection of indicators from initial blood routine test results to improve the accuracy of early prediction of COVID-19 severity

Abstract: The global pandemic of COVID-19 poses a huge threat to the health and lives of people all over the world, and brings unprecedented pressure to the medical system. We need to establish a practical method to improve the efficiency of treatment and optimize the allocation of medical resources. Due to the influx of a large number of patients into the hospital and the running of medical resources, blood routine test became the only possible check while COVID-19 patients first go to a fever clinic in a community hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…COVID-19 patients and healthy donors did not differ in regard to age, sex, race, or ethnicity. Peak WBC count was higher in patients who developed moderate to severe lung disease (14.36 ± 1.61 × 10 9 /L) versus patients who developed no/minimal lung disease (8.80 ± 0.86 × 10 9 /L, p < 0.01) consistent with a recently published prospective study in Wuhan that reported significantly higher WBC count in COVID-19 patients with severe-critically severe versus mild-moderate disease [ 37 ]. The reference range for (WBC) count is 4.5–11.0 × 10 9 /L.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…COVID-19 patients and healthy donors did not differ in regard to age, sex, race, or ethnicity. Peak WBC count was higher in patients who developed moderate to severe lung disease (14.36 ± 1.61 × 10 9 /L) versus patients who developed no/minimal lung disease (8.80 ± 0.86 × 10 9 /L, p < 0.01) consistent with a recently published prospective study in Wuhan that reported significantly higher WBC count in COVID-19 patients with severe-critically severe versus mild-moderate disease [ 37 ]. The reference range for (WBC) count is 4.5–11.0 × 10 9 /L.…”
Section: Resultssupporting
confidence: 87%
“…The baseline characteristics of each cohort are displayed in Table 1. [37]. The reference range for (WBC) count is 4.5-11.0 × 10 9 /L.…”
Section: Elevated Wbc Count In Covid-19 Patients With Moderate To Severe Lung Diseasementioning
confidence: 99%
“…Huyut et al [6], in a study of patients who died from COVID-19, showed that the ESR, INR, PT, CRP, D-dimer, and ferritin biomarkers are the most important biomarkers to detect the mortality of the disease. Luo et al [56] proposed a multi-criteria decision making (MCDM) algorithm combining ideal the solution similarity sequencing technique (TOPSIS) and naive Bayes (NB) as a feature selection procedure to predict the severity of COVID-19 from initial RBV values. With the MCDM model, the WBC, LYM, NEU values, and age were the most effective features in determining the severity of the disease with 82% accuracy obtained by ROC analysis [56].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple blood tests were shown to be associated with independent risk for poor ICU outcomes in COVID-19 patients. Elevated white blood cell count and neutrophils and low lymphocyte count are directly proportional to the severity of COVID-19 [17]. Moreover, elevated biomarkers of in ammation in COVID-19 namely: D-dimer, CRP, LDH, and ferritin, are independently associated with higher ICU admission, invasive ventilatory support, and death [18].…”
Section: Discussionmentioning
confidence: 99%